Odgovornost pravnih oseb za kazniva dejanja - zakonska ureditev in aktualne dileme - Šepec, Miha (Podjetje in delo, 2019)
Criminal law theory has been avoiding the regulation of criminal liability of legal persons for a long time. Legal persons are not capable of forming their own will and sense of guilt, which would justify criminal repression. And yet, today, the influence that legal persons have on our lives is simply too great that criminal law could afford to ignore legal persons altogether and still follow the principle of societas delinquere non potest. Criminal law therefore has a difficult task of carefully and clearly defining the basis of liability of legal persons and natural persons acting on behalf of or for the benefit of legal persons. The Criminal Code left the detailed regulation of these grounds to the Liability of Legal Persons for Criminal Offences Act, which is the only exception to the concept of the unity of the Criminal Code in Slovenian legal system. In addition to discussing the relationship between these two acts, the paper also examines current dilemmas of legal theory and case law. These are, in particular, how the concept of guilt regarding the responsibility of a legal person is understood, how the contributions of management, supervisory bodies, and employees of a legal person to a crime are dealt with, and how to define a plea bargain agreement when the one confessing to a crime is a legal person.
Keywords: criminal offence; governing bodies; guilt; kaznivo dejanje; krivda; liability of a legal person; nadzorni organi; odgovornost pravne osebe; plea agreement; sporazum o priznanju krivde; supervisory authorities; vodstveni organi